Investigating the Relationship between Critical Thinking Inclination and Progress Orientation with Entrepreneurial Traits among Abadan University of Medical Sciences Students - Jamshid Bahmaei; Bagher Pahlavanzadeh; Ameneh Khoshnazar; Ebrahim Kharazinejad (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Critical thinking and progress orientation are effective in developing entrepreneurial traits in undergraduate students. Therefore, this study was conducted with the aim of investigating the relationship between critical thinking tendency and progress goal orientation with entrepreneurial traits among students of Abadan University of Medical Sciences. Methods: The present study was a descriptive-analytical study. The statistical population of the study was the undergraduate students of Abadan University of Medical Sciences in 2022and 139 respondents were randomly selected. The research instruments included three questionnaires on critical thinking tendency, goal orientation of progress and measurement of entrepreneurship characteristics. To analyze the data from descriptive statistics (mean and standard deviation) and analytical statistics (two-sample t-tests (Mann-Whitney), analysis of variance (Kruskal-Wallis), correlation coefficient according to Pearson or Spearman) , the software SPSS. 26 was used with a significance level of 0.05. Results: A statistically significant correlation was found between the variables of entrepreneurial characteristics and goal-progress (P-value<0.001). In addition, a statistically significant correlation was found between the variables of the entrepreneurial characteristics and the tendency to think critically (P-value<0.001). The components performance avoidance (P-value <0.001) and performance-orientation (P-value = 0.002) from the variable goal-progress orientation with the components of the entrepreneurial characteristics, the components mental involvement (P-value < 0.001) and maturity (P-value < 0.001) from the variable tendency to critical thinking variable had a statistically significant correlation with the entrepreneurial characteristics. Conclusion: The results of this study show that tendency to critical thinking and goal-progress orientation are significantly related to entrepreneurial traits. Therefore, students with critical thinking characteristics discover and pursue economic and social situations in a more creative way and have the ability to innovatively choose the best and most effective ways to achieve entrepreneurial goals.